Separator for secondary battery having improved adhesion

CN122889960APending Publication Date: 2026-10-09LG ENERGY SOLUTION LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611041829.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-06-09
Filing Date
2022-06-07
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0009]专利文献1和2分别公开了一种隔板和一种制造所述隔板的方法,所述隔板被配置为使得无机颗粒和各种树脂彼此混合并在隔板基板上形成涂层,由此提高与电极的粘附力;然而,使用的粘合剂种类较多,包括多个粘合剂层,并且粘合剂的含量增加

Benefits of technology

[0030]从以上描述显而易见的是,根据本发明的用于二次电池的隔板具有以下效果:使用具有低密度的中空型粘合剂,由此容易地在隔板基板上进行浆料涂布,并且提高了所制造的隔板与电极之间的粘附力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122889960A_ABST
    Figure CN122889960A_ABST
Patent Text Reader

Abstract

The present invention relates to a separator for a secondary battery having improved adhesion. The present invention relates to a separator for a secondary battery having improved binding force with an electrode, and more particularly to a separator for a secondary battery including a porous polymer separator substrate and an inorganic layer disposed on at least one surface of the separator substrate, the inorganic layer including an inorganic material and a binder, wherein the binder is a hollow type binder.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese national phase application "202280006808.3" of PCT application PCT / KR2022 / 008023, filed on June 7, 2022, entitled "Separator for Secondary Batteries with Improved Adhesion". Technical Field

[0002] This application claims priority to Korean Patent Application No. 2021-0074549, filed on June 9, 2021, the disclosure of which is incorporated herein by reference in its entirety.

[0003] The present invention relates to a separator for a secondary battery having improved electrode adhesion properties and a method for manufacturing the separator, and more specifically to a separator having a hollow adhesive applied thereon, thereby improving the adhesion between the separator and the electrode. Background Technology

[0004] In lithium-ion batteries, the separator isolates the positive and negative electrodes from each other, preventing physical contact and thus internal short circuits. The separator also provides pathways for lithium-ion movement through micropores within its structure. Therefore, the separator plays a crucial role in the battery's safety and output characteristics. Safety Reinforced Separators (SRS separators), which offer improved safety, are widely used in lithium-ion batteries. SRS separators are configured to form a coating comprising inorganic materials and adhesives on a polyolefin-based substrate.

[0005] The adhesive is primarily made of PVDF-based polymers, and the separator is manufactured using a vapor-induced phase separation (VIPS) method. Currently produced SRS separators use PVDF-based adhesives, resulting in high adhesion to the positive electrode; however, styrene-butadiene rubber (SBR)-based adhesives exhibit lower adhesion to the negative electrode. Furthermore, because PVDF-based adhesives are hydrophobic, the separators have poor wetting properties in the electrolyte solution, thus reducing battery output.

[0006] Patent document 1 discloses a separator comprising a coating in an uncrosslinked state, the coating using a coating composition comprising specific amounts of crosslinkable and noncrosslinkable adhesives to improve the adhesion between the separator and the electrode.

[0007] The separator includes: an inorganic layer disposed on at least one surface of a porous polymer separator substrate, the inorganic layer comprising an inorganic material and a first adhesive; and an inorganic adhesive layer located between the separator substrate and the inorganic layer, the inorganic adhesive layer comprising a second adhesive configured to enhance the adhesion between the separator substrate and the inorganic layer.

[0008] Patent Document 2 discloses a separator for lithium secondary batteries, the separator having a porous coating on the surface of a porous polymer substrate to improve electrode adhesion and resistivity characteristics, the porous coating comprising inorganic particles and a binder polymer. In Patent Document 2, the PVdF-based binder comprises two PVdF binders mixed in a predetermined ratio, as can be seen by X-ray diffraction (XRD) analysis.

[0009] Patent documents 1 and 2 disclose a separator and a method for manufacturing the separator, respectively, wherein the separator is configured such that inorganic particles and various resins are mixed together and a coating is formed on the separator substrate, thereby improving adhesion to the electrode; however, a variety of adhesives are used, including multiple adhesive layers, and the adhesive content is increased.

[0010] (Existing technical documents)

[0011] (Patent Document 1) Korean Patent Application Publication No. 10-2020-0107602

[0012] (Patent Document 2) Korean Patent Application Publication No. 10-2021-0020798 Summary of the Invention

[0013] Technical issues

[0014] The present invention was made in view of the above problems, and the object of the present invention is to provide a separator for a secondary battery and a method for manufacturing the separator, the separator being configured such that the content of adhesive does not increase, thereby improving the adhesion to the electrodes without affecting the coating on the separator substrate.

[0015] Technical solution

[0016] The separator for a secondary battery according to the present invention, for achieving the above objectives, comprises a porous polymer separator substrate and an inorganic layer disposed on at least one surface of the separator substrate, the inorganic layer comprising an inorganic material and an adhesive, wherein the adhesive is a hollow adhesive.

[0017] In the separator for secondary batteries according to the present invention, the hollow adhesive may be an aqueous emulsion adhesive.

[0018] In the separator for secondary batteries according to the present invention, the aqueous emulsion adhesive may be an acrylic-based adhesive.

[0019] In the separator for secondary batteries according to the present invention, the hollow adhesive may have a particle size of 550 μm or less.

[0020] In the separator for secondary batteries according to the present invention, the hollow adhesive may have a density of 0.9 g / mL or less.

[0021] In the separator for secondary batteries according to the present invention, the acrylic adhesive may be at least one selected from the group consisting of acrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile.

[0022] In the separator for secondary batteries according to the present invention, the percentage of the adhesive in the inorganic layer may be 20% by weight or less.

[0023] The present invention provides a method for manufacturing a separator for a secondary battery, the method comprising: (S1) manufacturing a slurry, the slurry being configured such that the weight ratio of organic material to binder is 8:2 and the solid content of the slurry is 30%; (S2) fixing a separator substrate using a rod coater; (S3) applying the slurry manufactured in step (S1) to the edge of the separator substrate in a straight line “—” using a pipette; (S4) manipulating a rod to coat the slurry onto the separator substrate; and (S5) drying the coated slurry, wherein the slurry comprises a hollow binder having a density of 0.9 g / mL or less.

[0024] In the method of manufacturing a separator for a secondary battery according to the present invention, the hollow adhesive may have a particle size of 550 μm or less.

[0025] In the method of manufacturing a separator for a secondary battery according to the present invention, the hollow adhesive may be at least one selected from the group consisting of acrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile.

[0026] The method of manufacturing a separator for a secondary battery according to the present invention may further include manufacturing a hollow adhesive having a density of 0.9 g / mL or less prior to step (S1).

[0027] The present invention provides a battery cell including an electrode assembly configured such that a separator for a secondary battery is inserted between a positive electrode and a negative electrode.

[0028] Furthermore, the present invention can provide possible combinations of the above-mentioned solutions.

[0029] Beneficial effects

[0030] It is evident from the above description that the separator for secondary batteries according to the present invention has the following effects: the use of a hollow adhesive with low density facilitates the application of slurry onto the separator substrate and improves the adhesion between the manufactured separator and the electrode.

[0031] The process of coating the slurry onto the partition substrate is simple and does not require any additional complex steps, which is advantageous in terms of production process and manufacturing cost. Attached Figure Description

[0032] Figure 1 These are SEM images of non-hollow adhesives obtained using conventional methods.

[0033] Figure 2 This is a SEM image of the hollow adhesive according to the present invention. Detailed Implementation

[0034] Preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, enabling those skilled in the art to readily implement these preferred embodiments. However, in describing the operational principles of the preferred embodiments in detail, detailed descriptions of known functions and configurations included herein will be omitted where such descriptions may obscure the subject matter of the invention.

[0035] Furthermore, the same reference numerals will be used in all the accompanying drawings to refer to parts that perform similar functions or operations. Where the description throughout the specification states that one part is connected to another, this means not only that one part can be directly connected to the other, but also that one part can be indirectly connected to the other through yet another part. Moreover, including an element does not imply the exclusion of other elements, but rather means that, unless otherwise specified, these elements may be further included.

[0036] Furthermore, descriptions that specify elements by limiting or adding can be applied to all inventions unless otherwise specified, and do not limit any particular invention.

[0037] Furthermore, in the description of this invention and the claims of this application, the singular form is intended to include the plural form, unless otherwise stated.

[0038] Furthermore, in the description of this invention and the claims of this application, unless otherwise stated, "or" includes "and". Therefore, "including A or B" refers to three cases: including A, including B, and including both A and B.

[0039] In addition, all numerical ranges include the minimum value, the maximum value, and all intermediate values ​​in between, unless the context clearly indicates otherwise.

[0040] The present invention will be described in detail below.

[0041] The separator for a secondary battery according to the invention is configured to have a structure in which a coating is formed on at least one surface of a porous separator substrate, wherein the coating comprises an aqueous emulsion binder and a fluorinated nonionic surfactant as an additive.

[0042] The partition substrate can be a polyolefin-based partition commonly used in the art to which this invention pertains, and can be made of at least one selected from, for example, high-density polyethylene, low-density polyethylene, linear low-density polyethylene, ultra-high molecular weight polyethylene, polypropylene, polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polyethylenenaphthalene, and mixtures thereof.

[0043] In this invention, an inorganic layer is formed in the form of a layer on one or opposite surfaces of a porous separator substrate. The inorganic layer comprises inorganic particles and an aqueous emulsion binder, wherein the inorganic particles and the aqueous emulsion binder can be maintained in a bonded state, and the inorganic particles can be held bonded to the surface of the separator substrate by the aqueous emulsion binder.

[0044] In the present invention, the size of the inorganic particles of the inorganic layer is not limited, but may range from 0.001 μm to 10 μm, specifically 0.05 μm to 5 μm, more specifically 0.1 μm to 2 μm, so as to form an inorganic layer with a uniform thickness. The dispersibility of the inorganic particles having the above-specified size can be maintained, whereby it is easy to adjust the physical properties of the separator for a secondary battery and the phenomenon of thickness increase of the inorganic layer can be prevented.

[0045] The inorganic particles are not particularly limited as long as they are electrochemically stable. The inorganic particles are not particularly limited as long as no oxidation and / or reduction occurs within the operating voltage range of the electrochemical device to which the inorganic particles are applied. Specifically, when inorganic particles with ion transport capability are used, the ionic conductivity in the electrochemical device is increased, which is beneficial to performance improvement.

[0046] In the present invention, the inorganic material may be selected from BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1-x La x Zr 1- y Ti y O3 (PLZT) (0<x<1, 0<y<1), PB(Mg3Nb 2 / 3 )O3-PbTiO3 (PMN-PT), hafnium dioxide (H f O2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, TiO2, SiC, (LiAlTiP) x O y -based glass (0<x<4, 0<y<13), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2-based glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4), P2S5-based glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7), and at least one selected from the group consisting of mixtures thereof. However, the present invention is not limited thereto.

[0047] The aqueous emulsion adhesive according to the present invention can be used together with inorganic materials to form a coating for a separator, wherein the aqueous emulsion adhesive can maintain the bonding between inorganic particles and improve the adhesion between the electrode and the separator.

[0048] For example, aqueous emulsion adhesives can be acrylate-based adhesives and can have an average particle size of 550 μm or less.

[0049] Furthermore, there are no particular restrictions on the type of water-based emulsion adhesive, as long as the water-based emulsion adhesive does not cause a chemical change in the coating of the separator. For example, aqueous emulsion adhesives can be made from the following materials: polyolefins, such as polyethylene or polypropylene; fluorinated resins, such as polyvinylidene fluoride or polytetrafluoroethylene; fluorinated rubbers, such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers or ethylene-tetrafluoroethylene copolymers; styrene-butadiene copolymers and their hydrogenates; (meth)acrylate copolymers, such as methacrylate copolymers, acrylonitrile acrylate copolymers, or styrene acrylate copolymers; rubbers, such as ethylene propylene rubber; polyvinyl acetate; resins with a melting point or glass transition temperature of 180°C or higher, such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamide, polyimide, polyetheramide, polyester, aromatic polyester, or polyetheretherketone; polycarbonate; polyacetal; water-soluble resins, such as carboxyalkyl cellulose, alkyl cellulose, hydroxyalkyl cellulose, starch, polyvinyl alcohol, sodium alginate, polyethylene glycol, cellulose esters, polyacrylic acid, polyacrylamide, or polymethacrylic acid; or copolymers comprising two or more of these.

[0050] In this invention, the aqueous emulsion adhesive can be manufactured by dissolving at least one of the group consisting of acrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile in acetonitrile, which will be described in detail in the description of the manufacturing method, which will be described thereafter.

[0051] In the separator for secondary batteries according to the present invention, the coating may include additives, wherein the additives may be fluorinated nonionic surfactants.

[0052] Traditionally, various surfactants are known. For example, there are nonionic surfactants with alkyl groups as hydrophobic structural units; fluoroanionic surfactants, including sulfonates as hydrophobic structural units, which are among the fluoroanionic surfactants with fluorine atoms as hydrophobic structural units; and anionic surfactants such as quaternary ammonium salts. However, these surfactants do not reduce battery resistance; on the contrary, they have the property of increasing battery resistance.

[0053] Fluoro-based nonionic surfactants can be, for example, fluoroalkyl ethylene oxide adjuvants, fluoroalkenyl ethylene oxide adjuvants, fluoroalkyl propylene oxide adjuvants, fluoroalkenyl propylene oxide adjuvants, perfluoroalkyl ethylene oxide adjuvants, or perfluoroalkenyl ethylene oxide adjuvants.

[0054] Furthermore, the present invention provides a battery cell including an electrode assembly configured such that a separator for a secondary battery is inserted between a positive electrode and a negative electrode; wherein the battery cell may be a lithium secondary battery configured to have a structure in which the electrode assembly is impregnated with a non-aqueous electrolyte solution containing lithium salt.

[0055] For example, a positive electrode can be manufactured by applying a positive electrode mixture, including a positive electrode active material, to a positive electrode current collector and then drying the mixture. If necessary, binders, conductive agents, and fillers may be optionally added to the positive electrode mixture further.

[0056] Positive electrode current collectors are typically manufactured with a thickness ranging from 3 μm to 500 μm. There are no particular limitations on the type of positive electrode current collector, as long as it exhibits high conductivity and does not cause any chemical changes in the battery in which it is used. For example, the positive electrode current collector can be made of stainless steel, aluminum, nickel, titanium, or sintered carbon. Alternatively, it can be made of aluminum or stainless steel with a surface treated with carbon, nickel, titanium, or silver. Furthermore, the positive electrode current collector may have microscale irregular patterns formed on its surface to increase the adhesion of the positive electrode active material. The positive electrode current collector can be configured in any of a variety of forms, such as a film, sheet, foil, mesh, porous body, foam, and nonwoven fabric.

[0057] Positive electrode active materials are materials capable of inducing electrochemical reactions. Positive electrode active materials can be lithium transition metal oxides comprising two or more transition metals. For example, positive electrode active materials can be, but are not limited to: layered compounds such as lithium cobalt oxide (LiCoO2) or lithium nickel oxide (LiNiO2) substituted with one or more transition metals; lithium manganese oxides substituted with one or more transition metals; and materials with the chemical formula LiNi... 1-y M yLithium nickel-based oxides represented by O2 (where M = Co, Mn, Al, Cu, Fe, Mg, B, Cr, Zn or Ga, at least one of these elements is included, and 0.01≤y≤0.7); Li 1+z Ni b Mn c Co 1-(b+c+d) M d O (2-e) A e Lithium-nickel-cobalt-manganese composite oxides, such as Li, are defined as follows: (where -0.5≤z≤0.5, 0.1≤b≤0.8, 0.1≤c≤0.8, 0≤d≤0.2, 0≤e≤0.2, b+c+d<1, M=Al, Mg, Cr, Ti, Si or Y, and A=F, P or Cl). 1+z Ni 1 / 3 Co 1 / 3 Mn 1 / 3 O2 or Li 1+z Ni 0.4 Mn 0.4 Co 0.2 O2; or from chemical formula Li 1+x M 1-y M' y PO 4-z X z (where M = transition metal, preferably Fe, Mn, Co or Ni, M' = Al, Mg or Ti, X = F, S or N, -0.5≤x≤0.5, 0≤y≤0.5, and 0≤z≤0.1) represents olivine-based lithium metal phosphate.

[0058] Conductive agents are typically added such that, based on the total weight of the mixture including the positive electrode active material, the conductive agent accounts for 1% to 30% by weight. There are no particular limitations on the conductive agent, as long as it exhibits high conductivity in the battery in which it is applied without causing any chemical changes. Examples include graphite, such as natural or synthetic graphite; carbon black, such as acetylene black, Ketjen black, channel black, furnace black, lampblack, or thermal black; conductive fibers, such as carbon fibers or metal fibers; metal powders, such as fluorinated carbon powder, aluminum powder, or nickel powder; conductive whiskers, such as zinc oxide or potassium titanate; conductive metal oxides, such as titanium oxide; or conductive materials, such as polyphenylene derivatives, which can be used as conductive agents.

[0059] Adhesives are components that facilitate the bonding between active materials and conductive agents, as well as their bonding with current collectors. Based on the total weight of the mixture including the positive electrode active material, adhesives are typically added in amounts ranging from 1% to 30% by weight. Examples of adhesives that can be used include polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene terpolymers, sulfonated ethylene-propylene-diene terpolymers, styrene-butadiene rubber, fluororubber, and various copolymers.

[0060] Fillers are optional components used to suppress electrode expansion. There are no particular limitations on the filler, as long as it is made of fibrous material and does not cause chemical changes in the battery in which it is applied. Examples of fillers include olefin-based polymers such as polyethylene and polypropylene; and fibrous materials such as glass fiber and carbon fiber.

[0061] For example, a negative electrode can be manufactured by applying a negative electrode mixture, including a negative electrode active material, to a negative electrode current collector and then drying the mixture. Depending on the requirements, the aforementioned components, such as conductive agents, binders, and fillers, can be included in the negative electrode mixture.

[0062] Negative electrode current collectors are typically manufactured with a thickness ranging from 3 μm to 500 μm. There are no particular limitations on the negative electrode current collector, as long as it exhibits high conductivity and does not cause any chemical changes in the battery in which it is used. For example, the negative electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, or sintered carbon. Alternatively, it can be made of copper or stainless steel with a surface treated with carbon, nickel, titanium, or silver or aluminum-cadmium alloys. Furthermore, in the same manner as positive electrode current collectors, negative electrode current collectors can have microscale irregular patterns formed on their surface to increase the adhesion of the negative electrode active material. Negative electrode current collectors can be configured in any of a variety of forms, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics. For example, as negative electrode active materials, carbon, such as non-graphitized carbon or graphite-based carbon, and metal composite oxides, such as Li, can be used. x Fe2O3 (0≤x≤1), Li x WO2 (0≤x≤1), Sn x Me 1-x Me' y O z(Me: Mn, Fe, Pb, Ge; Me': Al, B, P, Si, elements of Groups 1, 2 and 3 of the periodic table, halogens; 0<x≤1; 1≤y≤3; 1≤z≤8); lithium metal; lithium alloys; silicon-based alloys; tin-based alloys; metal oxides, such as SnO, SnO₂, PbO, PbO₂, Pb₂O₃, Pb₃O₄, Sb₂O₃, Sb₂O₄, Sb₂O₅, GeO, GeO₂, Bi₂O₃, Bi₂O₄ or Bi₂O₅; conductive polymers, such as polyacetylene; or lithium cobalt nickel-based materials. The binder, the conductive agent and the optionally added components are the same as those described for the positive electrode.

[0063] Depending on the situation, a filler may be optionally added as a component for inhibiting the expansion of the negative electrode. There is no particular limitation on the filler, as long as the filler is made of a fibrous material and does not cause chemical changes in the battery in which the filler is applied. As examples of the filler, olefin-based polymers such as polyethylene and polypropylene; and fibrous materials such as glass fiber and carbon fiber may be used.

[0064] In addition, other components such as viscosity modifiers and adhesion promoters may be further optionally included or included in a combination of two or more thereof.

[0065] A viscosity modifier is a component that adjusts the viscosity of the electrode mixture, so that the process of mixing the electrode mixture and the process of applying the electrode mixture onto the current collector can be easily performed. Based on the total weight of the negative electrode mixture, the viscosity modifier may be added in an amount of up to 30% by weight. Carboxymethyl cellulose or polyvinylidene fluoride can be used as examples of the viscosity modifier. However, the present invention is not limited thereto. Depending on the situation, the solvents described above may also act as the viscosity modifier.

[0066] An adhesion promoter is an auxiliary component added to increase the adhesion of the active material to the current collector, and may be added in an amount of 10% by weight or less compared to the binder. For example, oxalic acid, adipic acid, formic acid, acrylic acid derivatives or itaconic acid derivatives can be used as the adhesion promoter.

[0067] Hereinafter, the present invention will be described with reference to the following examples. These examples are provided only for easier understanding of the present invention, and should not be construed as limiting the scope of the present invention.

[0068] <Manufacturing of non-hollow aqueous emulsion binder>

[0069] 20 ml of monomer and 200 ml of water were introduced into a container and stirred at 300 rpm. The mixture was heated under reflux for 3 minutes, and 0.2 g of potassium persulfate was added. The reaction was allowed to proceed for 2 hours until completion. After the reaction was complete, the mixture was centrifuged, and the separated solids were washed with ethanol.

[0070] <Manufacturing of Hollow-Type Waterborne Emulsion Adhesives>

[0071] Dissolve 6.0 mM acrylamide (AA), 24 mM ethylene glycol dimethacrylate (EGDMA), and 10 mg azobisisobutyronitrile (AIBN) in 50 ml of acetonitrile.

[0072] Carboxyl-capping polystyrene beads were introduced into the mixed solution and stirred at 700 rpm.

[0073] The reaction was carried out at 43°C for 12 hours, and then at 60°C for 24 hours.

[0074] Subsequently, the solids were aged at 85°C for 6 hours, centrifuged, and then washed with ethanol.

[0075] For washed solid materials, potassium persulfate is dissolved using THF to manufacture hollow adhesives.

[0076] The same hollow aqueous emulsion adhesive as described above is manufactured twice, thereby preparing hollow aqueous emulsion adhesive 1 and hollow aqueous emulsion adhesive 2.

[0077] Figure 1 These are SEM images of non-hollow adhesives based on conventional methods. Figure 2 This is a SEM image of the hollow adhesive according to the present invention.

[0078] The particle size and density of non-hollow adhesives according to conventional methods and hollow adhesives according to the present invention are shown in Table 1 below.

[0079] [Table 1]

[0080]

[0081] <Pulp Manufacturing>

[0082] As the inorganic layer to be applied to the porous partition substrate, inorganic materials, solvents, dispersants, and zirconia beads are mixed together for 2 hours. An aqueous emulsion binder is then added to the mixture, and the mixture is further mixed. Here, it is assumed that the total amount of the aqueous emulsion binder is 100% by weight, the weight ratio of inorganic materials to the aqueous emulsion binder is 8:2, and the solid content in the final slurry is 30%. Here, the solvent can be water.

[0083] <Example 1>

[0084] A moistened polypropylene separator substrate is fixed on a bar coater, and a slurry using the manufactured hollow aqueous emulsion adhesive 1 is applied in a straight line to the edge of the separator substrate using a pipette. The bar is then operated to uniformly apply the slurry to the separator substrate. The applied slurry is dried to produce a separator for secondary batteries with a coating thickness of 15.2 μm. Here, the slurry can be applied to one surface or the opposite surface of the separator substrate.

[0085] <Example 2>

[0086] The separator for the secondary battery was manufactured using the same method as in Example 1, except that the coating thickness was 13.3 μm.

[0087] <Example 3>

[0088] The separator for the secondary battery was manufactured using the same method as in Example 1, except that a hollow aqueous emulsion adhesive 2 was used and the coating thickness was 15.1 μm.

[0089] <Example 4>

[0090] The separator for the secondary battery was manufactured using the same method as in Example 3, except that the coating thickness was 13.2 μm.

[0091] <Comparative Example 1>

[0092] The separator for the secondary battery was manufactured using the same method as in Example 1, except that a non-hollow aqueous emulsion adhesive was used and the coating thickness was 15.4 μm.

[0093] <Comparative Example 2>

[0094] The separator for the secondary battery was manufactured using the same method as Comparative Example 1, except that the coating thickness was 13.2 μm.

[0095] Method for measuring the adhesion force between the separator and the electrode

[0096] A separator with a coating formed on it according to the comparative examples and embodiments of the present invention is stamped to a size of 2.5 cm x 7 cm, and a negative electrode is stamped to a size of 2.5 cm x 6 cm. The coated surfaces of the separator and the negative electrode are arranged facing each other and overlapped. A hot press is used at a temperature of 60°C and a pressure of 6.5 MPa to bring the separator and the negative electrode into close contact for one second, thereby attaching the separator and the negative electrode to each other. The separator-negative electrode sample is then attached to a slide glass with double-sided adhesive tape in a parallel manner.

[0097] The attached sample was mounted onto a UTM (LLOYD Instruments, AMETE) and subjected to a 180-degree peel test at a peel speed of 300 mm / min at room temperature to measure the adhesion force between the separator and the negative electrode sample. The results are shown in Table 2 below.

[0098] Air permeability measurement method

[0099] The partitions according to the comparative examples and embodiments of the present invention were stamped to a size of 5 cm x 5 cm, and the time required for 100 cc of gas to pass through the partition was measured using an Oken type air permeability measuring instrument EG01-55-1MR (Asahi Seiko Company). The results are shown in Table 2 below.

[0100] [Table 2]

[0101]

[0102] Those skilled in the art will understand that, based on the above description, various applications and modifications can be made within the scope of this invention.

Claims

1. A separator for a secondary battery, the separator comprising: Porous polymer separator substrate; and An inorganic layer disposed on at least one surface of the partition substrate, the inorganic layer comprising inorganic materials and an adhesive. The adhesive is a hollow adhesive.

2. The partition according to claim 1, wherein the hollow adhesive is an aqueous emulsion adhesive.

3. The partition according to claim 2, wherein the aqueous emulsion adhesive is an acrylic adhesive.

4. The partition according to claim 1, wherein the hollow adhesive has a particle size of 550 μm or less.

5. The partition according to claim 1, wherein the hollow adhesive has a density of 0.9 g / mL or less.

6. The partition according to claim 3, wherein the acrylic adhesive is at least one selected from the group consisting of acrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile.

7. The separator according to claim 1, wherein the percentage of the adhesive in the inorganic layer is 20% by weight or less.

8. A method for manufacturing a separator for a secondary battery, the method comprising: (S1) Prepare a slurry, wherein the slurry is configured such that the weight ratio of organic material to binder is 8:2, and the solid content of the slurry is 30%; (S2) Use a bar coater to fix the partition substrate; (S3) Using a pipette, apply the slurry prepared in step (S1) to the edge of the partition substrate in a straight line "—"; (S4) Operate the rod to coat the slurry onto the partition substrate; and (S5) Dry the coated slurry. The slurry comprises a hollow binder having a density of 0.9 g / mL or less.

9. The method of claim 8, wherein the hollow adhesive has a particle size of 550 μm or less.

10. The method of claim 8, wherein the hollow adhesive is at least one selected from the group consisting of acrylamide, ethylene glycol dimethacrylate and azobisisobutyronitrile.

11. The method of claim 8, further comprising: Before step (S1), a hollow adhesive with a density of 0.9 g / mL or less is prepared.

12. A battery cell comprising an electrode assembly configured such that a separator for a secondary battery according to any one of claims 1 to 7 is inserted between a positive electrode and a negative electrode.

Citation Information

Patent Citations

  • Separator having an improved dry adhesion with electrode and methode for manufacturing lithium secondary battery using the same

    KR1020200107602A

  • Lithium secondary battery separator with improved adhesiveness toward an electrode and Lithium secondary battery comprising the separator

    KR1020210020798A